Interest and career choice of selected college students as determined by Holland's Personality Orientation - Bantang, Joanne Reandelar (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2003)
The study was conducted to explore the relationship of the chosen career of college students to personality styles and interests. The sample consisted of 110 students selected through purposive sampling. Data were gathered with the use of a researcher-developed opinionnaire based on Holland's theory. The analytical techniques employed in the study were descriptive statistics and Spearman Rank- order correlation analysis. Careers of the subjects were found correlated to their respective personality orientations supporting Holland's classification system of career and occupation. Among the recommendations made are exposing students to career planning, being introspective of their interests and abilities, and considering all factors critical to career decisions. Refining the opinionnaire to reflect more of the Filipino-based careers will be a good follow-up. Significant information may still be uncovered upon expanding sample size and using more complicated statistical methods.